Mitochondrial oxygen metabolism as a potential predictor of weight loss after laparoscopic sleeve gastrectomy for class III obesity - Engelmann, Markus; Götze, Juliane; Baumbach, Philipp; Neu, Charles; Settmacher, Utz; Ardelt, Michael; Kissler, Hermann; Coldewey, Sina M. (Frontiers in Endocrinology, 2025)
The prevalence of obesity is increasing at an alarming rate in industrialized countries. Obesity is a systemic disease that causes not only macroscopic alterations, but also mitochondrial dysfunction. Laparoscopic sleeve gastrectomy (LSG) poses a potential therapeutic option for patients with severe obesity. In order to ascertain the efficacy of bariatric interventions, it is important to assess not only weight loss, but also changes in body composition. Additionally, the aim of this study was to investigate the association between weight loss and cellular oxygen metabolism, a surrogate for mitochondrial function. We used bioimpedance analysis (BIA) to assess changes in weight and body composition in patients up to one year after LSG. To evaluate mitochondrial oxygen metabolism, we used the Cellular Oxygen Metabolism Monitor (COMET) to non-invasively measure the mitochondrial oxygen tension (mitoPO2), mitochondrial oxygen consumption (mitoVO2) and mitochondrial oxygen delivery (mitoDO2). We compared the values obtained in patients with obesity with those of age- and sex-matched healthy controls and investigated changes up to one year after LSG. 48 patients (46.5 years [35.5-55.3]; 38/48 female (79.2%); BMI 46.7 [42.5-51.0]) completed the study. They showed a significant weight loss and a decrease in relative fat mass after six months. We found no differences in mitochondrial oxygen metabolism between obese patients and healthy controls. MitoPO2, mitoVO2 and mitoDO2 did not change up to one year after surgery. It is noteworthy that patients who exhibited higher mitoPO2, mitoVO2, and mitoDO2 values prior to surgery demonstrated superior weight loss outcomes one year after LSG. This was the first study to investigate the non-invasively measured mitochondrial oxygen metabolism in the long-term course after bariatric surgery. Further studies in larger cohorts are needed to confirm these findings.Clinical trial registrationhttps://www.bfarm.de/DE/Das-BfArM/Aufgaben/Deutsches-Register-Klinischer-Studien/_node.html, identifier DRKS00015891.